2005
DOI: 10.1021/ic048618n
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phosphorus Ligand NMR Probes To Investigate Electronic and Second-Sphere Solvent Effects in Ligand Substitution Reactions at Manganese(II) and Manganese(III)

Abstract: Manganese/ligand association dynamics were studied using a series of structurally related anionic phosphorus ester ligand probes [CH(3)OP(O)(X)(Y)(-), where X = CH(3)O, CH(3)CH(2), or H and Y = O, S, or BH(3)]. Reactions of the probe ions with Mn(H(2)O)(6)(2+) and a manganese(III) porphyrin (Mn(III)TMPyP(5+)) were studied in aqueous solution by paramagnetic (31)P NMR line-broadening techniques. A satisfactory linear free energy relationship for reactions of the probe ions with Mn(H(2)O)(6)(2+) and Mn(III)TMPyP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This is corroborated by the fact that axial aqua ligands for Mn III porphyrins in aqueous solution are very labile. For example, the rate for displacement of an aqua ligand in Mn III TM-4-PyP by various phosphorus ligands was measured by Summers et al using 31 P NMR line-broadening techniques and ligand exchange rates ranging from 5 × 10 5 to 9 × 10 6 M −1 s −1 …”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by the fact that axial aqua ligands for Mn III porphyrins in aqueous solution are very labile. For example, the rate for displacement of an aqua ligand in Mn III TM-4-PyP by various phosphorus ligands was measured by Summers et al using 31 P NMR line-broadening techniques and ligand exchange rates ranging from 5 × 10 5 to 9 × 10 6 M −1 s −1 …”
Section: Discussionmentioning
confidence: 99%
“…That effect alone is sufficient for bringing the rate constants to the same order of magnitude. Furthermore, it was shown that the aromatic groups of the porphyrins provide a hydrophobic environment that may also change the accessibility of central metal ions to the negatively charged species involved in the above mentioned dismutation and reduction processes, 41 as well that the charges of the complexes are either above or below the plane, which channels the negativelycharged reactants toward the axial positions of Mn porphyrin more efficiently. 6 Both of the latter two effects are entirely ignored in the application of the Fuoss equation.…”
Section: T P T T T T Tmentioning
confidence: 99%
“…A comprehensive study of reactions between [CH 3 OP(O)(X)(Y)] À , X = CH 3 O, CH 3 CH 2 or H and Y = O, S or BH 3 and [Mn(H 2 O) 6 ] 3+ or [Mn III (TMPyP)] 5+ using paramagnetic 31 P NMR line-broadening shows that the reactions with the aqua complex involve an I d mechanism, crucially involving H-bonding with the aqua ion in the formation of an outer-sphere species, so that the rate was not sensitive to ligand basicity. 89 Although the reaction with the [Mn III (TMPyP)] 5+ is also dissociative, it is modified by the porphyrin's hydrophobic environment, decreasing basicity and hydrophilicity and increasing reaction rates. Rates of reaction of [Mn III (TEPyP)] and [Mn III (TPPS)] with HNO donors are rapid, k = B10 5 M À1 mol À1 , but they react slowly, if at all, with NO donors, allowing discrimination between them.…”
Section: Six-coordinationmentioning
confidence: 99%